Association of HIV Infection with Biomarkers of Kidney Injury and Fibrosis in the Multicenter AIDS Cohort Study. Issue 5 (July 2017) - Jotwani, Vasantha; Scherzer, Rebecca; Estrella, Michelle M; Jacobson, Lisa P; Witt, Mallory D; Palella, Frank; Ho, Ken; Bennett, Michael; Parikh, Chirag R; Ix, Joachim H; Shlipak, Michael
Background: Chronic kidney disease (CKD) is common among HIV-infected individuals but serum creatinine is insensitive for detecting kidney damage at early stages. We hypothesized that HIV infection would be associated with elevations in subclinical markers of kidney injury and fibrosis in a contemporary cohort of men. Methods: In this cross-sectional study, we measured urine levels of interleukin-18 (IL-18), kidney injury molecule-1 (KIM-1), pro-collagen type III N-terminal pro-peptide (PIIINP) and albumin-creatinine ratio (ACR) in 813 HIV-infected and 331 uninfected men enrolled in the Multi-center AIDS Cohort Study. Results: Median eGFR was 95 ml/min/1.73 m 2 among African-Americans ( n =376) and 87 ml/min/1.73 m 2 among Caucasians ( n =768). Among HIV-infected men, the median CD4 lymphocyte count was 572 cells/mm 3 and 76% of men had undetectable HIV RNA levels. After multivariable adjustment for traditional CKD risk factors including eGFR, HIV infection was associated with 52% higher urine IL-18 (95% CI, 33%, 73%), 44% higher KIM-1 (27%, 64%), 30% higher PIIINP (15%, 47%) and 84% higher ACR (54%, 120%), with similar effect sizes among African-Americans and Caucasians ( P >0.2 for tests of interaction by race). These associations remained statistically significant in analyses that excluded persons with detectable HIV RNA levels and in models that adjusted for cumulative exposure to tenofovir disoproxil fumarate. Conclusions: Compared with uninfected men, HIV-infected men had more extensive glomerular and tubulointerstitial damage, as assessed by urine biomarkers. Future studies should evaluate whether combinations of biomarkers can be used to monitor stages of kidney injury and to predict CKD risk in HIV-infected individuals.